Clinical case of congenital aplasia cutis - T.N Plekhanova; J.A Bigma; V.L. Belozerova; Y.A Mozgova; S.O. Drobich (Bukovynian State Medical University, 2013)
The article submitted review of the literature and description of a clinical case of the rare defect ‒ congenital aplasia of the skin. Discussed the clinical features of the disease, causes, classification, treatment approaches, particularly surveillance.